PENGARUH KINERJA KEUANGAN DAN DIGITALISASI KEAMANAN TERHADAP KEPUASAN NASABAH BRILINK : STUDI KASUS PADA AGEN BRILINK EN MANDIRI - Dwi Wahyu Setyaningsih; Aris Eddy Sarwono (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of financial performance and digital security on customer satisfaction at BRILink EN Mandiri Agent. The research uses a quantitative survey method involving 100 respondents. Regression analysis shows that both financial performance and digital security have a significant and positive influence on customer satisfaction. These findings highlight the importance of improving digital security systems and financial management to enhance customer satisfaction and loyalty.